Buddha Sasana Dan Hamemayu Hayuning Bawana Dalam Konteks Masyarakat 5.0 - wardani, Niken; Johny (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya Wonogiri, 2025)
This article examines how the values of the Buddhist Sasana and the Javanese philosophy of